Analysis of School Principals' Academic Supervision in Improving Teacher Performance at SMP Negeri 1 Bengkalis - Mukhtar, Mukhtar; Supardi, Supardi; Rahmawati, Rahmawati (STKIP PGRI SITUBONDO, 2024)
This research aims to find out and analyze in depth the performance of academic supervision carried out by school principals in improving teacher performance at SMP N 1 Bengkalis. The research method uses qualitative data collection techniques using observation, interviews and conclusions. The results of the research show that in planning academic supervision, information was obtained that the principal always gave authority to teachers to appreciate their innovations in teaching. The principal also visited the teacher's room. In order to check directly the state of teacher development in preparing administration. Supervision of the implementation of supervision by the school principal uses the Sigum application where with this application teachers will be given the ease of uploading data and increasing the use of science and technology. The supervision activities that will be carried out by the school principal are well structured. The implementation of academic supervision by the principal does not reduce the assessment of the principal as a supervisor who helps teachers improve teacher performance. Coaching and training is one of the forms provided by school principals which is a manifestation not of judging teachers but rather directing teachers' skills to be more capable of innovation. Preparation of syllabus, prota, process, lesson plans and preparation of effective teaching hours. Apart from that, the principal provides direction to teachers in the form of motivation for teachers, which is able to provide encouragement to develop teacher performance in their respective competencies. The role of the principal to provide input, ideas or forms of warning is a good attitude to achieve educational progress at SMP N 1 Bengkalis. Academic supervision has been carried out by the school principal through many stages, such as direct coaching, face-to-face and online (on the network). The principal also provides maximum direction at the end of the evaluation. Because there will be visible deficiencies in the learning process. These deficiencies are used to process and analyze the evaluation results. Based on the results of interviews and observations, providing guidance on learning evaluation as a form of follow-up. This guidance is carried out directly by supervisors and school principals during the evaluation. If the principal and supervisory team find teachers who are having difficulty carrying out learning evaluations, the team will try to overcome this